The optimal use of tildrakizumab in the elderly via improvement of Treg function and its preventive effect of psoriatic arthritis - Fukasawa, Takemichi; Yamashita, Takashi; Enomoto, Atsushi; Norimatsu, Yuta; Toyama, Satoshi; Yoshizaki-Ogawa, Asako; Tateishi, Shoko; Kanda, Hiroko; Miyagawa, Kiyoshi; Sato, Shinichi; Yoshizaki, Ayumi (Frontiers in Immunology, 2023)
As a form of precision medicine, this study aimed to investigate the specific patient population that would derive the greatest benefit from tildrakizumab, as well as the mechanism of action and efficacy of tildrakizumab in reducing the occurrence of psoriatic arthritis (PsA). To achieve this, a multi-center, prospective cohort study was conducted, involving a population of 246 psoriasis patients who had not received any systemic therapy or topical finger therapy between January 2020 and April 2023. Two independent clinicians, who were blinded to the study, analyzed nailfold capillary (NFC) abnormalities, such as nailfold bleeding (NFB) and enlarged capillaries, as well as the incidence of new PsA. Additionally, the factors that determined the response of psoriasis after seven months of tildrakizumab treatment were examined. The study also examined the quantity and role of regulatory T cells (Tregs) and T helper 17 cells both pre- and post-treatment. The severity of psoriasis, as measured by the Psoriasis Area and Severity Index (PASI), was found to be more pronounced in the tildrakizumab group (n=20) in comparison to the topical group (n=226). At 7 months after tildrakizumab treatment, multivariate analysis showed that those 65 years and older had a significantly better response to treatment in those achieved PASI clear or PASI 2 or less (Likelihood ratio (LR) 16.15, p<0.0001; LR 6. 16, p=0.01). Tildrakizumab improved the number and function of Tregs, which had been reduced by aging. Tildrakizumab demonstrated significant efficacy in improving various pathological factors associated with PsA. These factors include the reduction of NFB, enlargement of capillaries, and inhibition of PsA progression. The hazard ratio for progression to PsA was found to be 0.06 (95% confidence interval: 0.0007-0.46, p=0.007), indicating a substantial reduction in the risk of developing PsA. Tildrakizumab's effectiveness in improving skin lesions can be attributed to its ability to enhance the number and function of Tregs, which are known to decline with age. Furthermore, the drug's positive impact on NFB activity and capillary enlargement, both of which are recognized as risk factors for PsA, further contribute to its inhibitory effect on PsA progression.